Baicalin's Therapeutic Time Window of Neuroprotection during Transient Focal Cerebral Ischemia and Its Antioxidative Effects In Vitro and In Vivo. (25th June 2013) - Cheng, Fafeng; Lu, Yi; Zhong, Xianggen; Song, Wenting; Wang, Xueqian; Sun, Xiaoguang; Qin, Jianguo; Guo, Shaoying; Wang, Qingguo
Abstract : We investigated the effects of baicalin on an ischemia-reperfusion-induced brain injury model in rats and its antioxidative activities in vitro and in vivo . An ischemia-reperfusion injury of the brain via a middle cerebral artery occlusion (MCAO) was induced in rats. Baicalin was injected at different time points (0, 2, 4, and 6 h) after the MCAO was induced. Baicalin can improve neurological function and significantly decrease brain infarction within a time window of 4 h. Moreover, baicalin was able to reduce cell apoptosis and had the strong antioxidative effect of reducing reactive oxygen species production and malondialdehyde generation. In contrast, baicalin interfered with superoxide dismutase and nicotinamide adenine dinucleotide 2′-phosphate oxidase activities. Moreover, baicalin also exhibited strong neuroprotective effects against H2 O2 -mediated injury and improved the SOD activity of neurons. Furthermore, baicalin demonstrated good scavenging of hydroxyl radicals, superoxide anions, and DPPH radicals and exerted an additional effect of inhibiting xanthine oxidase. Baicalin showed beneficial effects against MCAO-induced injury within a 4 h time window, and its antioxidative effects both in vitro and in vivo may partly elucidate its mechanism of action.